Design of algorithm to optimize irregular geometries for 3D printing - Lam, Jiong Le (2018)
The utilisation of the conventional extrusion based 3D printers in the medical industry has been rapidly increasing. However, there are limitations for medical applications that might be ignored in the traditional fabrication process. As an example, while printing a model by Fused Deposition Modelling (FDM), the Z-axis resolution is a limiting factor while printing irregular geometries where the gradient of the curve is non-linear producing a jagged surface which is not ideal. In this literature, curvature analysis techniques are utilised to determine a path where a seam will be made within the irregular geometrical object. The path, determined by feature extraction algorithms, will be marked for a cut to flatten the computer aided design (CAD) model using an add-on to facilitate the user experience for new users to the open sourced programme (Blender) before it is 3D printed. This approach allows the increase in resolution precision for 3D printing using conventional FDM machines and addresses one of the challenges faced in conventional extrusion-based 3D printers for 3D models with irregular curvature.